Management Practices of Cooperatives: Roadmap Towards Improved Performance and Sustainability - Jumawan, April R. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The pandemic has demonstrated the cooperatives’ preparation, preparedness, and ability to respond to the needs of their members and the community. The study aimed to assess the level of management practices observed by the cooperatives and to identify constraints faced in their operations before and during the pandemic. A quantitative research method was used. Interviews were performed in person and over-the-phone. Survey questionnaires were developed and put through a pilot test. Moreover, a Google form link was provided to respondents who wished to respond online. Minitab, a statistical tool, was used to aid with all data analysis. It has been discovered that cooperatives can significantly enhance their financial performance by properly managing their working capital, capital structure, and capital budgeting. Non-financial management techniques were also significant to cooperatives’ development. This work, in particular, provides vital information for comprehending the intricacies of many topics connected to cooperative operations.